Settlement of Waqf Disputes and its Asset Protection in East Java, Indonesia (UINSI Samarinda, 2021)
Waqf is commonly defined as an endowment made by Muslims to a religious cause. By this definition, waqf is a spiritual practice with a divine aspect for Muslim people. In Indonesia, the implementation of Waqf is regulated in national law and adjacent to a kind of private law. Because waqf is similar to a sort of private law in Indonesia, it is possible for waqf in the future to have a dispute around property rights dissatisfaction. This article determines a determinant factor of waqf disputes in Indonesia, especially East Java. This article is an empirical legal study by looking at phenomena background of the waqf dispute and mapping out a model of waqf dispute resolution overcame by several parties. This article finds that waqf disputes in Indonesia are caused by several determinant factors, such as recognition of ownership of the founder’s family (wāqif), changes in the aims and objectives of waqf assets, and abandonment waqf assets. The result of this study reveals that maṣlalah – as a principle of Islamic law objectives – becomes a consideration in formulating a model of waqf dispute resolution. Efforts to resolve waqf disputes are often taken in two ways: first, legalizing waqf assets through religious courts. Second, the conflicts are usually resolved through either formal or informal mediation processes. Thus, litigation and non-litigation of legal process play an active role in resolving waqf disputes in Indonesia. Keywords: Waqf, settlement of waqf dispute, maṣlahah, waqf assets in Indonesia.